Analysis of gravity heat pipe for anti-icing and snow melting on road surface. (August 2019) - Qing, Qian; Zhang, Deng-Chun; Chen, Da-Wei
Abstract: Road icing is a serious hazard to highway traffic safety, so it is necessary to develop the anti-icing and de-icing technology. In this paper, theoretical and simulation analysis was carried out based on the idea that the gravity heat pipe uses shallow geothermal energy to meet the requirements of highway de-icing. The maximum heat transfer limit of different working media was calculated, and the two-dimensional pavement heat transfer model and thermal resistance model were established. The effect of different pipe diameters, pipe spacing and length of evaporation and condensation section on the heat transfer efficiency of gravity heat pipe to the surface of road was considered. It is concluded that ammonia can maximize the heat transfer limit of heat pipe due to its high latent heat, which is the best working fluid for preventing ice and snow melting of gravity heat pipe. When the pipe spacing is 150mm, the road surface temperature can be more than 2 °C. Considering the maximum heat transfer per unit area, the optimal length of the gravity heat pipe is 30m for the evaporation section and 10m for the condensation section, and the unit heat transfer is 205W/m 2 .